Optimal Configuration of Hybrid Energy System for Rural Electrification of Community Healthcare Facilities - Saheed Lekan Gbadamosi (Applied Sciences, 2022)
The unavailability of a constant power supply has been a major problem in remote communities in Africa as it impedes the proper operation of healthcare facilities in these locations. This has deprived inhabitants of free access to good healthcare services, thereby resulting in an increase in maternal and child mortality rates in rural communities in Africa. Therefore, in order to address this problem and render a life-saving intervention for rural dwellers and to also improve their healthcare service delivery, this paper focuses on the optimal configuration of a hybrid energy system for the rural electrification of community healthcare facilities. It presents an analysis of an off-grid hybrid energy system comprised of diesel generators, wind turbines and solar PV with a battery storage system to meet the energy demand of healthcare facilities in a remote community in Nigeria. In this study, hybrid energy systems are considered owing to the high reliability and availability of the intensity of solar radiation and wind speeds in Nigeria. An optimization model was developed which seeks to minimize the operational cost of hybrid energy systems. The proposed model was implemented using four case studies and solved using algebraic modeling language. The results obtained from the sensitivity analysis indicate that the configuration that includes solar PV, wind turbines, a battery storage system and a diesel generator provides the optimum power required for a rural healthcare center with a suitable energy cost and emission reduction from the system of diesel generators.